2017
DOI: 10.1016/j.cois.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory learning and chemical ecology of olfaction in disease vector mosquitoes: a life history perspective

Abstract: Mosquitoes transmit many debilitating diseases including malaria, dengue and Zika. Odors mediate behaviors that directly impact disease transmission (blood-feeding) as well as life history events that contribute to mosquito survival and fitness (mating and oviposition, nectar foraging, larval foraging and predator avoidance). In addition to innate olfaction-mediated behaviors, mosquitoes rely on olfactory experience throughout their life to inform advantageous choices in many of these important behaviors. Prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
44
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 95 publications
2
44
0
1
Order By: Relevance
“…Despite being repulsive during baseline conditions, skatole at 100 μg/l could be attractive for gravid Aedes aegypti females if previously reared in water containing this chemical. These results verified that early experience of mosquitoes at aquatic stage could have an impact in the adult mosquito life 7,43 . As previously reported 15,16 for Anopheles malaria vectors, the dissociation between oviposition site, which is often scarce, and remote food source implies needs for long or mid-range orientation and would necessitate “some form of learnt behaviour” 15 .…”
Section: Discussionsupporting
confidence: 78%
“…Despite being repulsive during baseline conditions, skatole at 100 μg/l could be attractive for gravid Aedes aegypti females if previously reared in water containing this chemical. These results verified that early experience of mosquitoes at aquatic stage could have an impact in the adult mosquito life 7,43 . As previously reported 15,16 for Anopheles malaria vectors, the dissociation between oviposition site, which is often scarce, and remote food source implies needs for long or mid-range orientation and would necessitate “some form of learnt behaviour” 15 .…”
Section: Discussionsupporting
confidence: 78%
“…To detect and locate suitable hosts, mosquitoes rely on multiple sensory cues, including olfactory, visual, and thermosensory information [1][2][3][4][5] while flying through a dynamic environment [6]. Whereas responses to olfactory (for review [7][8][9]) and, to a lesser extent, thermal stimuli [10,11] have been well studied, comparatively less is known about how visual cues evoke behavioural responses in mosquitoes (but see [12,13]) and how olfaction and vision are integrated. A recent study showed that CO2 detection activates a strong attraction to visual features that is critical for mediating interaction with close-range cues like heat and other host volatiles [3].…”
Section: Resultsmentioning
confidence: 99%
“…Food scarcity is an important ecological constraint on mosquito larvae [26] , but little is known about the chemosensory mechanism of foraging in larval mosquitoes. Given the relative simplicity of the larval nervous system, understanding chemosensory signal transduction, coding, and behavior in larvae could lead to novel control interventions and enable a more holistic understanding of mosquito behavior in areas such as food seeking and chemotaxis [17,24] .…”
Section: Main Text Introductionmentioning
confidence: 99%
“…Food scarcity is an important ecological constraint on mosquito larvae [26] , but little is known about the chemosensory mechanism of foraging in larval mosquitoes. Given the relative simplicity of the larval nervous system, understanding chemosensory signal transduction, coding, and behavior in larvae could lead to novel control interventions and enable a more holistic understanding of mosquito behavior in areas such as food seeking and chemotaxis [17,24] .Notwithstanding, as of recently, we have lacked effective genetic tools to study mosquito larval sensory systems as they process environmental information. Current tools used in mosquitos to monitor neural activity include extracellular recording from sensilla and antennal lobe cells [27] , as well as using synthetic calcium-sensitive dyes (e.g., FURA-2) in vivo or in heterologous systems [28,29] .…”
mentioning
confidence: 99%
See 1 more Smart Citation